2012 Ninth International Conference on Information Technology - New Generations 2012
DOI: 10.1109/itng.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source Sandbox for Increasing the Accessibility of Functional Programming to the Bioinformatics and Scientific Communities

Abstract: Scientists are continually faced with the need to express complex mathematical notions in code. The renaissance of functional languages such as LISP and Haskell is often credited to their ability to implement complex data operations and mathematical constructs in an expressive and natural idiom. The slow adoption of functional computing in the scientific community does not, however, reflect the congeniality of these fields. Unfortunately, the learning curve for adoption of functional programming techniques is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It has been shown that these features, together with other amenities like powerful debugging tools that Lisp programmers take for granted, offer a significant productivity boost to programmers [ 3 ]. Lisp also gives programmers the ability to implement complex data operations and mathematical constructs in an expressive and natural idiom [ 69 ].…”
Section: Other Unique Strengthsmentioning
confidence: 99%
“…It has been shown that these features, together with other amenities like powerful debugging tools that Lisp programmers take for granted, offer a significant productivity boost to programmers [ 3 ]. Lisp also gives programmers the ability to implement complex data operations and mathematical constructs in an expressive and natural idiom [ 69 ].…”
Section: Other Unique Strengthsmentioning
confidence: 99%
“…However, BioClojure does not have functions for SAM/BAM manipulation and is not fully implemented in Clojure. The CONNJUR-Sandbox source [ 11 ] contains examples of the visualization of protein structures using PDB data in Clojure and the prediction of neighboring amino acids with Support Vector Machine algorithms named Clojure Amino Acid Predictor.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that these features, together with other amenities like powerful debugging tools that Lisp programmers take for granted, offer a significant productivity boost to programmers [54,55]. Lisp also gives programmers the ability to implement complex data operations and mathematical constructs in an expressive and natural idiom [56].…”
Section: Other Unique Strengthsmentioning
confidence: 99%